برنامج مشاوراة لتعليم القراءة في المعهدالعناية باسوروان - Tibbil Qulub, Ahmad; Nuril Mufidah, (Shaut al Arabiyyah, 2023)
Arabic is a very important language for millions of Islamic people around the world both Arabic and non-Arabic, Al- inayah pasuruan islamic boarding school is one of the islamic boarding schools that creates cadres of islamic cadres and cadres of the nation by equipping their students with learning arabic. The existence of pesantren as an uplifting educational institution is increasingly challenged to improve itself in every activity carried out in the islamic boarding school, for example in teaching practice. The learning program is one of the important factors in the continuity of learning Arabic. for successful teaching relating to the program used. Deliberations have various implementations of types of deliberations that take place in Islamic boarding schools, including as learning methods, batshul masa'il, and programs. As a learning method, deliberation has similarities with the method of class discussion or group discussion. The main problems of this study are: How is the implementation in qira'ah learning in pesantren ? This type of research is a qualitative research design of data collection in this study using observation, interviews and field notes. In this study, researchers chose the caregivers of Al Inayah Pasuruan Islamic Boarding School as informants.